Spesifikasi Kebutuhan Perangkat Lunak Sistem Informasi E-Survey Badan Litbang dan Diklat Kementerian Agama dengan standar ISO/IEC/IEEE 29148:2018 - Andi Muh Fais Farid; Nuryasin, Ilyas (Infotek: Jurnal Informatika dan Teknologi, 2024)
The digitalization of survey processes is crucial in today's era, and this research aims to design the software requirements specification for the E-Survey Information System for the Research and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia. The methodology employed follows the ISO/IEC/IEEE 29148:2018 standard in developing the System Requirements Specification (SRS) document. This comprehensive SRS outlines the purpose, scope, product overview, user characteristics, limitations, functional requirements, non-functional requirements, database design, interface, and use case diagrams. The functional requirements encompass survey management, survey question management, user management, role management, and accessing surveys. Non-functional requirements address performance and user-friendliness aspects. The result is a detailed SRS document that serves as a guideline for the development team in building an integrated and modern E-Survey application. This application will streamline and digitize the survey activities conducted by the Research and Training Agency, enabling efficient data collection, processing, and analysis. By following industry standards, the developed system aims to enhance productivity, centralize survey operations, and support informed decision-making processes related to strengthening religious moderation and harmony among religious communities in Indonesia